2018
DOI: 10.1186/s12881-018-0662-1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study showing no association between G238A (rs361525) tumor necrosis factor-α (TNF-α) gene polymorphism and its serum level, hormonal and biochemical aspects of polycystic ovary syndrome

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is the main cause of female infertility. Interactions among genetic, biochemical, and immunological factors can affect the pathogenesis of PCOS. As a proinflammatory cytokine, tumor necrosis factor-α (TNF-α) plays an important role in this regard. The present study aimed to evaluate the association of the rs361525 gene single-nucleotide polymorphism (SNP) and TNF-α serum levels with the hormonal and biochemical characteristics of PCOS in Iranian individuals.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Our findings showed that TNF- α level was significantly associated with Prx4. The presence of chronic inflammation may activate this defense process by affecting the antioxidant system [ 13 ]. Chronic inflammatory markers enhance insulin resistance and hyperandrogenism; therefore, those are involved in the pathogenesis of PCOS [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed that TNF- α level was significantly associated with Prx4. The presence of chronic inflammation may activate this defense process by affecting the antioxidant system [ 13 ]. Chronic inflammatory markers enhance insulin resistance and hyperandrogenism; therefore, those are involved in the pathogenesis of PCOS [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF- α is a proinflammatory cytokine, which is secreted by granulose-luteal cells, ovarian macrophages, and immune cells [ 11 ]; it interferes in inflammation and immune responses [ 12 ]. TNF- α has a role in PCOS patients with obesity and hyperandrogenism [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…82 As the interaction between TNF and INS exists in Figure 4C, there may be an implication of TNF polymorphism associated with PCOS development, but the high serum levels of TNF-alpha were definitively increased in PCOS patients. 83,84 TNFalpha is especially high in obesity-PCOS compared with normalweight female subjects. 85 The different mechanisms modulated by TNF-alpha and IL-6 negatively affect insulin signaling, via decreased adiponectin signaling and glucose transporter type 4 protein, which effect is exacerbated in the endometrium of obese PCOS women leading to an abnormal endometrial response to androgen and insulin stimulation and consequently leading to a reproductive failure.…”
Section: Discussionmentioning
confidence: 99%
“…A study among Iranian women reported that there may be an association between PCOS susceptibility and IL17A rs2275913 and IL32 rs9927163 SNPs 101 . However, another Iranian study found no significant association between PCOS and the rs361525 polymorphism of the TNF gene 102 . According to a meta‐analysis of PCOS studies, the risk of this disorder is not associated with the –1031 T/C, –308G/A, or –805C/T polymorphism of TNF 103 .…”
Section: Inflammationmentioning
confidence: 99%
“…101 However, another Iranian study found no significant association between PCOS and the rs361525 polymorphism of the TNF gene. 102 According to a meta-analysis of PCOS studies, the risk of this disorder is not associated with the -1031 T/C, -308G/A, or -805C/T polymorphism of TNF. 103 Another study similarly reported that there is probably no association between PCOS susceptibility and the -308G/A sequence variation of TNF.…”
Section: Infl Ammationmentioning
confidence: 99%